O trágico em Fábula de Anfion, de João Cabral de Melo Neto - Fabio Feldman dos Santos Freitas (2009)
This dissertation presents an interpretation of the poem Fábula de Anfion, written by João Cabral de Melo Neto, identifying the tragic substrate depicted from its plot. In a first moment, I delimit the philosophical implications of the concept of tragic, according to a critical examination of certain themes worked on idealist and post-idealist philosophy. Afterwards, I try to analyze how, in a way, Cabrals poem represents a tragic view of the word and how this fact can be associated to fundamental aspects of the poetics developed by the writer.